The current state of food allergy therapeutics. Issue 10 (3rd October 2017) - Chen, Meng; Land, Michael
ABSTRACT: The prevalence of IgE mediated food allergy is an increasing public health concern. The current standard of treatment is strict avoidance of the offending food(s). There are no FDA approved treatments for food allergy. This review will provide an overview of strategies currently under investigation for the treatment of food allergy. The main focus of research has been directed at various forms of immunotherapy, including oral, sublingual and epicutaneous delivery routes. While oral immunotherapy (OIT) has shown the greatest promise for efficacy in terms of amount of protein that can be ingested, it has also demonstrated less tolerability and a less favorable safety profile as compared to sublingual immunotherapy (SLIT) and epicutaneous immunotherapy (EPIT), which offers the least protection but has the best safety and tolerability profile. Investigation is also underway for modified antigens that may be used for immunotherapy and for adjuncts that may help facilitate immunotherapy, including biologics such as anti-IgE therapy, and also probiotics. There are also a number of preclinical concepts that are being evaluated to manipulate the antigens and/or the immune system that may one day be translatable to patients.